Developing a challenge-based corrosion e-book to enhance vocational students’ concept understanding and creative thinking skills - Sjaeful Anwar; Santi Deva; Ijang Rohman; Harianti Harianti; Ropi Marlina; Billy Oktora Abdillah Fauzi (Jurnal Cakrawala Pendidikan, 2026)
This study aimed to develop a challenge-based corrosion e-book with a chassis coating context using the Four Steps Teaching Material Development (4STMD) method and to evaluate its effectiveness in enhancing vocational students’ concept understanding and creative thinking skills. A design and development research approach was employed, comprising design, development, and evaluation phases. The e-book was developed through the 4STMD stages of selection, structuring, characterization, and didactic reduction, yielding ten concept labels on corrosion and redox reactions contextualized within automotive chassis maintenance. The product was validated by expert reviewers and tested with 20 grade-XI students of a Light Vehicle Engineering program at a vocational school in Bandung, Indonesia. Expert evaluation indicated that the e-book was highly feasible across content, language, presentation, and graphic criteria. Student comprehensibility reached an average of 92%. A one-group pretest–posttest design with the Wilcoxon signed-rank test revealed statistically significant improvements (α = 0.05) in both concept understanding and creative thinking skills, the latter measured through Torrance’s indicators of fluency, flexibility, originality, and elaboration. A Spearman correlation of r = .985 confirmed a very strong positive relationship between the two outcomes. These findings demonstrate that integrating challenge-based learning with the 4STMD method in a vocationally relevant e-book effectively supports higher-order thinking in chemistry education for vocational students.